(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Uremic pruritus is one of the most common disabling symptoms in patients with end-stage renal disease. We aimed to study the effect of montelukast sodium for the treatment of uremic pruritus lasting more than 3 months in patients undergoing hemodialysis and compare it with placebo. Methods and Materials. Eighty patients undergoing hemodialysis at 3 centers in Shiraz, Iran, were recruited to a randomized double-blinded controlled trial to receive 10 mg of montelukast or placebo, daily for 30 days. To assess the severity of pruritus, a visual analogue scale and the Detailed Pruritus Score, based on a combined score of severity and distribution of pruritus and sleep disturbance, were used. Sleep disturbance, severity, and distribution scores were added up to calculate the patients’ final score at the start and the end of the study. Results. The mean reduction of visual analogue scale score was significantly greater in the montelukast group (2.73 ± 2.03) compared to that in the placebo group (5.47 ± 2.37, P < .001). Mean reduction in Detailed Pruritus Score was also greater in the montelukast group (3.24 ± 2.2 versus 6.44 ± 3.25, respectively, P < .001). The mean high-sensitivity C-reactive protein in the montelukast group decreased from 5.48 ± 3.86 µg/mL to 3.86 ± 3.58 µg/mL, while it increased in the placebo group from 6.69 ± 4.49 µg/mL to 8.14 ± 5.20 µg/mL. Conclusions. Montelukast can be an add-on therapy in uremic pruritus, especially when pruritus is refractive to other treatments.